The Intensity Use of Social Media "Y" and Academic Stress to Students’ Academic Procrastination - Basori, Muchamad Adam; Sulfia, Sulfia (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
In everyday life, procrastination behavior is often found in society, one of the causal factors can be time management problems such as using social media "Y" with high intensity. Related studies have examined this idea but found inconsistencies from the results of previous research because researchers suspect that there are variables that influence this inconsistency and are motivated to research the correlation between the intensity of social media "Y" and academic stress on academic procrastination. This research uses a correlational design with a quantitative approach. The research results found a simultaneous correlation between the intensity of use of social media "Y" and academic stress on academic procrastination. In addition, a partial correlation was found in a positive direction between academic stress and academic procrastination, but there was no partial correlation between the intensity of use of social media "Y" and academic procrastination. The use of social media "Y" by students shows a form of diversion that is carried out to vent the feelings of pressure felt during the study period, so that students tend to procrastinate or refuse to complete assignments, and they can understand the importance of stress management to minimize academic procrastination behavior.